Developing the Technology of Fruit Chips for Dietary Nutrition - Smolnikova, Farida; Kassymov, Samat; Rotanov, Evgeny; Konovalov, Viktor; Nelyubina, Elena; Grigoryants, Igor; Bobkova, Elena (International Journal of Psychosocial Rehabilitation, 2024)
Fruit chips are an alternative to potato chips and are becoming increasingly popular in the human diet. In this paper, a review of the scientific works on the preparation of fruit chips from apples, bananas, pears, peaches, and persimmons is conducted. The recipe for making fruit chips from apples and bananas with cinnamon and sesame is developed. The technological scheme of preparation and organoleptic evaluation of chips is described. The main useful properties of developed fruit chips are highlighted.